Prognostic Value of 24‐Hour Ambulatory ECG (Holter) Monitoring in Boxer Dogs. (16th May 2013) - Mõtsküla, P.F.; Linney, C.; Palermo, V.; Connolly, D.J.; French, A.; Dukes McEwan, J.; Luis Fuentes, V.
<x xml:space="preserve">Abstract</x> Background Boxer dogs are reported to be predisposed to arrhythmogenic right ventricular cardiomyopathy (ARVC), but the natural history has not been well characterized and inconsistent diagnostic criteria have been applied to identify affected dogs. Echocardiographic examination findings are unremarkable in many affected Boxer dogs, and in these dogs, 24‐hour ambulatory ECG (Holter) monitoring often is used for diagnostic and prognostic purposes, despite limited information available relating Holter findings to outcome. Hypothesis/Objectives Boxers with complex ventricular arrhythmias at initial presentation will have shorter survival times. The objective was to investigate the prognostic value of Holter monitoring in Boxer dogs. Animals One hundred and twenty‐two Boxer dogs seen at 3 university referral hospitals. Methods Retrospective study. Survival times were obtained for Boxer dogs evaluated by echocardiography and a 24‐hour Holter ECG. Kaplan‐Meier survival analysis was used to estimate the median survival time and Cox proportional hazards analysis was used to identify variables independently associated with cardiac mortality. Results Outcome data were obtained for 122/163 dogs meeting the inclusion criteria. Of the 70 dogs that had died, 45 were considered to have suffered cardiac‐related deaths. Median survival was significantly longer in dogs with a left ventricular systolic diameter (LVIDs) ≤ 35 mm compared with those with LVIDs > 35 mm (P < .001). Multivariable analysis in dogs with LVIDs ≤ 35 mm showed that the presence of ventricular tachycardia, age >4.5 years, and male sex were independent predictors of cardiac mortality. Conclusions and Clinical Importance Holter monitoring in Boxer dogs provides valuable prognostic information.